Improving Marketing Performance through Green Innovation Value Creation as a Pathway to Sustainability for Small and Medium Enterprises in the Modern Era - Mulyono, Hardi; Hutasuhut, Julianto; Indrawan, Muhammad Gita; Nainggolan, Solawati; Fikri, Muhammad Hilman (Business Management Analysis Journal (BMAJ), 2025)
Environmental challenges are increasingly pressing, prompting Small and Medium Enterprises (SMEs) to adopt sustainable practices. According to the Indonesian Central Statistics Agency, SMEs contribute 97% of the workforce, yet only a small fraction implement environmentally friendly practices. This research investigates how SMEs can leverage green innovation to enhance marketing performance and promote sustainability. It employs a quantitative approach to assess the relationship between green innovation, green marketing, and marketing performance among SMEs in Medan City. The findings reveal that green innovation and value creation significantly influence green competitive advantage, with an R² value of 0.807. While green marketing does not directly relate to marketing performance, green innovation substantially affects it. Additionally, green competitive advantage is a partial mediating variable, indicating SMEs' potential to develop innovative sustainable marketing strategies that create competitive value and encourage environmental responsibility. The study underscores the critical role of green innovation in transforming SME marketing approaches, positioning sustainable practices as key differentiators in competitive markets.